The Effects of Competence, Work Experience, and the Work Environment on Employee Performance - Misran Hadi; Armalia Reny WA; Hasbullah Hasbullah; Andi Surya; Desmon Desmon; Yudhinanto CN (Goodwood Publishing, 2026)
Purpose: The purpose of this study is to examine the individual and combined effects of competence, work experience, and the work environment on employee performance, particularly in public sector institutions where service quality and accountability are crucial.Method: The study utilized a quantitative research design, collecting primary data from all employees of the Way Tenong District Office in West Lampung Regency. A census (saturation sampling) approach was employed, where the entire population was included in the study sample. Hypotheses were tested using multiple linear regression analysis to assess both partial and simultaneous relationships between the variables. Results: The results indicate that competence, work experience, and the work environment have significant positive effects on employee performance. Additionally, the three variables together explained a substantial portion of the variance in employee performance. Conclusions: The study concludes that strengthening employee competencies, leveraging work experience, and creating a supportive work environment are key to enhancing employee performance in public sector organizations. Limitations: The study may have limitations in terms of its focus on a single district office, which may affect the generalizability of the findings to other regions or sectors. Contributions: This study contributes to the understanding of factors influencing employee performance in the public sector, providing valuable insights for improving the effectiveness of public sector institutions through targeted interventions in competence development, work experience, and work environment improvements.